Illness beliefs and locus of control: a comparison of patients with pseudoseizures and epilepsy. - Stone, J; Binzer, M; Sharpe, M (2004)
PURPOSE: The aim of this study was to examine the illness beliefs and locus of control of patients with recent onset pseudoseizures and to compare these with patients with recent onset epilepsy. METHODS: Twenty consecutive patients with pseudoseizures of recent onset (mean duration 5.4 months) were compared with 20 consecutive patients with recent onset epilepsy on their responses to (a) the Illness Behaviour Questionnaire (IBQ) and (b) a measure of locus of control, a dimension of the tendency to attribute events to internal or external factors. RESULTS: In comparison with patients with epilepsy, patients with recent onset pseudoseizures believed that psychological factors were less important than somatic ones were (P < .005) and had a greater tendency to deny nonhealth life stresses (P < .0001). No significant differences were detected in disease conviction or illness worry. Patients with pseudoseizures had a more external locus of control (P < .001), CONCLUSIONS: Patients with pseudoseizures are less likely than those with epilepsy to see psychological factors as relevant to their symptoms, more likely to deny that they have suffered from life stress and also to have a more external locus of control. The implications for treatment are discussed.